A comparison of motivation to learn English between English major and non-English major students in a Vietnamese university. Issue 2 (4th May 2017) - Ngo, Huong; Spooner-Lane, Rebecca; Mergler, Amanda
ABSTRACT: Despite the plethora of literature examining higher education students' motivation to learn a second language, it is not known if students who choose to study English as their major differ from those who are required to study English as the minor component of their wider degree. Drawing on self-determination theory, this paper reports on the findings of a quantitative study designed to investigate the types of motivation demonstrated by English major ( n  = 180) and non-English major students ( n  = 242), and their levels of effort expended in learning English in a Vietnamese university. The findings revealed that both groups demonstrated high levels of motivation to learn English to prepare for their future profession. English major students felt more intrinsically motivated and less obligated to learn English. In addition, for both groups, intrinsically motivated students invested the highest levels of effort in learning English. This paper argues that it is imperative for lecturers to foster students' intrinsic aspirations to learn English to improve the quality of the teaching and learning of English in Vietnamese higher education.